An Electrochemical Sensor Based on Molecularly‐Imprinted‐Polymer‐Modified Carbon Quantum Dots@hexagonal Boron Nitride Nanosheets Nanocomposites for Triclosan Determination. Issue 22 (9th June 2022) - Wang, Ziwei; Wu, Haiyan; He, Yuhao; Yan, Yu; Zhou, Wenjuan; Zhang, Guohua; Liu, Dan; Ye, Zhaolian; Qiu, Fengxian
Abstract: An electrochemical sensor based on carbon quantum dots@hexagonal boron nitride nanosheets nanocomposites (CQDs@HBNNS‐NCs) and molecularly imprinted polymer (MIP) was proposed for the triclosan (TCS) analysis. The CQDs@HBNNS‐NCs were utilized as the modifier, which exhibited excellent electrochemical properties. The MIP film was prepared in situ in the presence of template (TCS) and monomer ( o ‐phenylenediamine) to provide the specific molecular recognition. The CQDs@HBNNS‐NCs were characterized by transmission electron microscopy (TEM), X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FT‐IR), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Under the optimal conditions, the current response was linear with the logarithmic value of TCS concentration in the range of 2 nM–0.1 mM, and the limit of detection (LOD) was calculated as 0.005 μM (S/N=3). Furthermore, the proposed electrochemical sensor showed favorable selectivity, stability, and was used for the TCS analysis in tap water samples with decent accuracy. Abstract : This paper developed a molecularly imprinted polymer electrochemical sensor for triclosan (TCS) analysis. The electrochemical sensor platform was fabricated by assembling carbon quantum dots@hexagonal boron nitride nanosheets nanocomposites (CQDs@HBNNS‐NCs) and molecularly imprinted polymer film modified a glass carbon electrode. The as‐prepared sensor exhibited a wide linear range with a relatively low detection limit and satisfactory selectivity.